Inclusive governance of hydropower on shared rivers? Toward an international legal geography of the Lower Mekong basin - Hensengerth, Oliver (Frontiers in Climate, 2024)
Hydropower is now the largest source of renewable energy worldwide. The International Renewable Energy Agency estimates that current hydropower capacity will need to double by 2050 in order to transition to net zero and to arrest the rise of global temperatures at 1.5 degrees Celsius. Much of the currently built and planned dams are on rivers shared between two or more countries. This raises the risk of increased inter-state conflict. However, to exploit hydropower peacefully, the impact on local communities must also be considered. This foregrounds the need to build inclusive institutions that can mediate the different interests, norms and values held by communities located across different scales.Shared river basins are characterized by a legal pluralism that includes laws, rules and procedures developed by international water law, multilateral development banks, national governments, multinational corporations, transnational non-governmental organizations, and local riverine communities. These actors are often in conflict, but they also align in complex ways, where hydropower development on shared rivers is concerned. In many basins, such as the Lower Mekong, river basin organizations are tasked with the development of shared water resources. It is therefore important that these institutions are inclusive and mediate the different interests and values of user communities located across different scales.To understand how river basins organization can mediate the legal pluralism in a shared river basin, the article develops an international legal geography approach to analyzing water governance. In doing so, it expands the scope of legal geography to the study of complex ecosystems for which there are no fixed jurisdictional boundaries. A legal geography approach to the study of water governance in shared river basins considers the ways in which law, space, and society are intertwined in the production of laws, rules and procedures for water access and allocation. In doing to, it brings legal geography into a conversation with the literature on international water law and ecosystems governance. It then applies this framework to the case study of the Lower Mekong basin.